Metastatic small bowel occlusion as initial presentation of squamous cell carcinoma of the lung - Rita Seara Costa; Ana Luísa Vieira; Juliana M. Costa; Beatriz Fernandes; Aníbal Ferreira (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Costa RS, Vieira AL, Costa J, Fernandes B, Ferreira A. Metastatic small bowel occlusion as initial presentation of squamous cell carcinoma of the lung. Turk J Gastroenterol 2019; 30(5): 492-4.